2012
DOI: 10.1186/1746-6148-8-76
|View full text |Cite
|
Sign up to set email alerts
|

Correlation among genetic, Euclidean, temporal, and herd ownership distances of porcine reproductive and respiratory syndrome virus strains in Quebec, Canada

Abstract: BackgroundPorcine reproductive and respiratory syndrome (PRRS) is a viral disease that has a major economic impact for the swine industry. Its control is mostly directed towards preventing its spread which requires a better understanding of the mechanisms of transmission of the virus between herds. The objectives of this study were to describe the genetic diversity and to assess the correlation among genetic, Euclidean and temporal distances and ownership to better understand pathways of transmission.ResultsA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…Although the magnitude and significance of the correlation coefficients do not change, it is important to account for the effect of ownership, given the association between ownership and genetic distance and the spatial aggregation of herds within the same ownership. This finding is similar to what was detected in a study from Québec (Lambert et al., ). First, in the Québec study, the correlation between sequence distance and spatial separation was not significant when continuous distance measures were considered.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although the magnitude and significance of the correlation coefficients do not change, it is important to account for the effect of ownership, given the association between ownership and genetic distance and the spatial aggregation of herds within the same ownership. This finding is similar to what was detected in a study from Québec (Lambert et al., ). First, in the Québec study, the correlation between sequence distance and spatial separation was not significant when continuous distance measures were considered.…”
Section: Discussionsupporting
confidence: 93%
“…The Mantel test was used to test the Spearman rank correlation between geographic distance, temporal distance and sequence distance using the vegan package (version 1.15, http://cran.r-project.org/web/packages/vegan/index.html) in R (version 2.09). The partial Mantel test makes it possible to test correlation between two variables while adjusting for a third variable that may be correlated with both main variables (Goldberg et al., ; Mondaca‐Fernandez et al., ; Lambert et al., ). The partial Mantel statistic was used to test correlation between geographic, temporal and sequences distances; sequentially including each of these variables as the ‘adjusting’ variable.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies relied on serologic evidence of PRRSV circulation in various herd types. Some investigators have relied on descriptive statistics, 41,140 contingency tables, 40 Cox proportional hazard models, 73,142 generalized additive models and methods to detect spatial and space-time clustering and clusters commonly used in spatial epidemiology, 141 statistical models of individual-level infectious disease transmission, 35 results of the Mantel correlation test, 39,[143][144][145] and linear regression based on a permutation approach. 40,[143][144][145] The analytic approach has also differed among studies.…”
Section: Control and Elimination Programs At The Farm Levelmentioning
confidence: 99%
“…Investigators of epidemiological studies 40,77 identified area spread and argued that aerosol transmission played a critical role in transmission. 141 Few studies have been conducted to investigate membership in important networks such as ownership, 35,41,141,144,145 sources of animals and semen, 35,77,140,141 or transportation or service providers. Furthermore, several authors reported the possibility of area spread for some discrete genotypes, although such spread was not identified as the dominant mechanism of spread 41,141 or could be explained in some cases because of common sources of animals.…”
Section: Control and Elimination Programs At The Farm Levelmentioning
confidence: 99%